The Effect of Educational Protocol Intended to Promote Illness Perception on Death Anxiety in Patients with Heart Failure: A Clinical Trial Study - Negin Babaei Vahed; Mahin Roohani; Saeedeh Zenoozian; Elham Faghihzadeh; Kourosh Amini (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Exposure to death and the resulting anxiety is a significant dimension of the mental health of patients suffering from chronic diseases, including heart failure. Objectives: Illness perception affects adherence to health-promoting behaviors and health outcomes. Hence, the purpose of this study was to investigate the effect of a perception-based intervention on death anxiety in patients with heart failure. Methods: Following a randomized clinical trial design, 120 patients suffering from heart failure, recruited using convenient sampling, were categorized into two groups of control and intervention using the randomized minimization method. The intervention group received three 30-minute sessions of training, while the control group only received routine interventions. Data were collected using a demographic information checklist, brief illness perception questionnaire (BIPQ), and Templer Death Anxiety Scale. Data analysis was administered by independent t-test, paired t-test, chi-square, and Wilcoxon tests using SPSS version 22. Results: There was a significant difference between the study groups concerning anxiety scores before and after the intervention (P<0.001). Death anxiety scores before the intervention were not significantly different between the two groups (P=0.640), but there was a statistically significant difference in death anxiety scores after the intervention (P<0.001). Conclusion: Regarding the importance of death anxiety in patients with heart failure, this study demonstrated the importance of using perception-based interventions.